Investigating Indonesian EFL pre-service teachers’ conceptions of culture and intercultural competence - Arief Eko Priyo Atmojo; Tomy Kartika Putra (Universitas Syiah Kuala, 2022)
Globalization inevitably increases communication among people from different languages and cultural backgrounds. This phenomenon dramatically demands changes in the traditional aims of language teaching which rely on the norms and values of native-speaking countries. A large body of literature encourages language teaching to be concerned more with intercultural competence (hereinafter IC), which is allegedly effective to help students achieve successful intercultural communication. Nonetheless, in the Indonesian context, there is still an iota of evidence regarding pre-service teachers’ understandings of the terms culture and IC. Thus, this study attempts to gain insights into Indonesian English as a Foreign Language (EFL) pre-service teachers’ understandings of culture and IC. It is considered as a single case study employing questionnaires and interviews. In total, 26 EFL pre-service teachers participated in this study by answering a questionnaire, with mainly close-ended and some open-ended questions. From these participants, seven pre-service teachers were interviewed. The results suggested the discrepancy in the participants’ understandings of culture and IC. This condition may hinder the meaningful goals of cultural teaching and the effective pedagogical practices in their future EFL classrooms. Drawing on the results, the present study provides some recommendations for the pre-service teachers and teacher education in an attempt to develop cultural teaching in English Language Teaching (ELT).